1999
DOI: 10.1152/ajplung.1999.276.3.l501
|View full text |Cite
|
Sign up to set email alerts
|

Expression of heat shock protein 72 by alveolar macrophages in hypersensitivity pneumonitis

Abstract: The current study was done to look at a possible role of heat shock proteins (HSPs) in hypersensitivity pneumonitis (HP). The specific aims were to determine whether there was a difference in the expression of HSP72 in alveolar macrophages (AMs) between mice challenged with HP antigen and saline-treated control mice and between AMs obtained by bronchoalveolar lavage from 18 patients with HP and 11 normal subjects. The expression of HSP72 was studied under basal conditions and under a mild heat shock. HSP72 exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…Racine et al showed that alveolar macrophages (AMs) from challenged mice with antigens from Saccharopolyspora rectivirgula (SR) exhibited increased basal level of HSP70 compared to control mice. However, a second stimulation with SR-antigen on these AMs, did not further enhance HSP70 levels in sensitized mice compared to control mice, which showed much higher HSP70 levels [60]. The absence of HSP70 response to an additional stress in HP mice could be explained by the altered immunoregulatory activity observed during HP.…”
Section: Hypersensitivity Pneumonitis (Hp)mentioning
confidence: 75%
“…Racine et al showed that alveolar macrophages (AMs) from challenged mice with antigens from Saccharopolyspora rectivirgula (SR) exhibited increased basal level of HSP70 compared to control mice. However, a second stimulation with SR-antigen on these AMs, did not further enhance HSP70 levels in sensitized mice compared to control mice, which showed much higher HSP70 levels [60]. The absence of HSP70 response to an additional stress in HP mice could be explained by the altered immunoregulatory activity observed during HP.…”
Section: Hypersensitivity Pneumonitis (Hp)mentioning
confidence: 75%